Meridional Overturning Circulation Transport Variability at 34.5°S During 2009–2017: Baroclinic and Barotropic Flows and the Dueling Influence of the Boundaries - Meinen, Christopher S. (2018)
Six years of simultaneous moored observations near the western and eastern boundaries of the South Atlantic are combined with satellite winds to produce a daily time series of the basin-wide meridional overturning circulation (MOC) volume transport at 34.5°S. The results demonstrate that barotropic and baroclinic signals at both boundaries cause significant transport variations, and as such must be concurrently observed. The data, spanning ~20 months during 2009–2010 and ~4 years during 2013–2017, reveal a highly energetic MOC record with a temporal standard deviation of 8.3 Sv, and strong variations at time scales ranging from a few days to years (peak-to-peak range = 54.6 Sv). Seasonal transport variations are found to have both semiannual (baroclinic) and annual (Ekman and barotropic) timescales. Interannual MOC variations result from both barotropic and baroclinic changes, with density profile changes at the eastern boundary having the largest impact on the year-to-year variations.